Neural Nets WIRN11: Proceedings of the 21st Italian Workshop on Neural Nets - Apolloni, Bruno (IOS, 2013)
This book is a collection of selected papers from the 21st WIRN workshop, held in Vietri sul Mare, Italy, in 2011. This workshop is the annual meeting of the Italian Neural Network Society (SIREN) where participants can discuss and analyze the latest challenges in the wider field of neural networks. The papers, all of which are the peer reviewed original results of the authors, are divided into three groups: applications, models and specific signal processing implementations. These are followed by contributions to the three additional special sessions: models of behavior for human-machine interaction, autonomous machine learning and neuromorphic engineering. Providing an insight into the latest news and ideas from a group of international experts, this volume will be of value to all those with an interest in neural networks and related fields. This book is published in the subseries Knowledge-Based Intelligent Engineering Systems (KBIES).